PH and lipid unsaturation impact the formation of acrylamide and 5-hydroxymethylfurfural in model system at frying temperature. (September 2019) - Wang, Yuting; Hu, Huiyu; McClements, David Julian; Nie, Shaoping; Shen, Mingyue; Li, Chang; Huang, Yousheng; Zhong, Yadong; Chen, Jie; Zeng, Maomao; Xie, Mingyong
Abstract: The effect of unsaturated free fatty acids (FFAs) and triglycerides (TGs) on the formation of acrylamide and 5-hydroxymethylfurfural (HMF) at frying temperature was investigated. We hypothesized that the nature of the precursors generated by the Maillard reaction in the presence of FFAs and TGs, such as the Amadori product and α-dicarbonyl compounds, would impact acrylamide and HMF formation. Interestingly, the initial pH of the aqueous phase impairs the observed effect of the addition of lipids on the formation of acrylamide. Addition of FFAs and TGs increased acrylamide formation in non-buffered systems (distilled water, pH 4.6), but decreased it in buffered systems (sodium acetate, pH 6.0). Conversely, incorporation of these lipids promoted HMF formation under both conditions. The degree of fatty acid unsaturation played an important role in the formation of acrylamide and HMF. The effect of unsaturated lipids on the acrylamide and HMF was due to lipid oxidation. Statistical correlations were made between acrylamide and HMF formation and α-dicarbonyl compounds in the presence of unsaturated lipids. Graphical abstract: Unlabelled Image Highlights: The impact of unsaturated lipids on acrylamide and HMF formation was studied. Lipids reduced acrylamide in non-buffered models but increased it in buffered ones. HMF yield increased with FA unsaturation. Lipids addition increased Fructose-Asparagine yield. By impacting dicarbonyl yield, lipid subsequently impacted that of acrylamide and HMF.